Rewrite the following as a product of two factors

a(a -1) + 5(a - 1) =

Skip to content# Rewrite the following as a product of two factorsa(a -1) + 5(a – 1) =

Mathematics ##
Comments (3) on “Rewrite the following as a product of two factorsa(a -1) + 5(a – 1) =”

### Leave a Reply Cancel reply

Rewrite the following as a product of two factors

a(a -1) + 5(a - 1) =

investment b is an ordinary annuity with $3,909.64 in the account after one year.

step-by-step explanation:

4a-5=0

4a=5

a=1.25

Product of 2 factors:

Unknown, as ive worked for about 30 minutes and can't figure it out

Step-by-step explanation:

2a-1a+5a-5

4a-5=0

a=1.25

ur mom

step-by-step explanation: